Patients' Perspectives on Factors that Influence Diabetes Self-Care - E Shakibazadeh; B Larijani; D Shojaeezadeh; A Rashidian; MH Forouzanfar; LK Bartholomew (Tehran University of Medical Sciences, 2011)
Background: Although diabetes mellitus is of high concern in Iran, and the level of control is unacceptable, few qualitative studies have been carried out to reflect the experiences of patients on the barriers and motivators to self-care. This study aimed to explore a culturally based experience of Iranian diabetic patients regarding the personal and environmental barriers to and facilitating factors for diabetes self-care. Methods: Six focus groups were conducted among type 2 diabetic patients in the Charity Foundation for Special Diseases' diabetes clinic. Purposeful sampling was used. Newly diagnosed patients (less than six months) and all type 1 diabetic patients were excluded. Three focus groups were held on for each sex. A total of 43 patients participated in the study. Framework analysis was used to extract the themes from the data. Results:Data analysis showed five main barriers: physical barriers (such as physical effects of diabetes); psychological barriers (such as health beliefs); educational barriers (such as lack of knowledge about diabetes); social barriers (such as group pressure); and care system barriers (such as service availability). Along with the barriers, there were some motivators that the participants mentioned as a stimuli to control their diabetes. They include beliefs about diabetes, perceived responsibility for family, religious beliefs, and the views of significant others. Conclusion:Culturally based interventions are needed to improve diabetes care management in Iran. In addition to personal factors, diabetes health educators should pay attention to the environmental factors when they develop programs.